Stuoy of the effects of cations on chloride caused corrosion of steel in concrete - Farzammehr, H.; Dehghanian, Ch.; Locke, C. E. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
There have been differences observed in chloride ion behavior in concrete depending on the type of associated cation. This paper, which combines an electrochemical study with a pare solution analysis is study, is concreted with determining the effects of cations on chloride caused corrosion of steel in concrete. The effect of CaCl2 and NaC1 (mixed in Type 1 Portland cement concret) on corrosions of steel in concrete was investigated using electrochemical techniques such as anodic potentiodynamic polarization and linear polarization. The results and indicated that the corrosion of steel in calcium chloride contaminated concrete was more severe than in sodium chloride cantaminated concrete. This observation was made at equal chloride ion concentrations which were in the range of O to 2.1 percent base on weight of concrete. in the pore in solution analysis study the effects of CaC12 and NaC1 (mixed in type I Portland cement paste on compotitions of the pore solution, associared with hardened cement pastes with chloride ion concentration ranging from 0.036 to 1 percent, based on the weight of the cement, were expressed at times ranging from 28 days to 84 days after casting and analyzed to determine chloride, sodium, calcium and hydroxyl ion concentrations. The pH of the pore solution increased with increased amount of NaCl. The addition of CaC12 had the opposite effect. The chloride ion concentrations in the pare solutions associate with pastes containing NaCl2 were higher than in the ones associated with CaCl2 contaminated pastes. The chloride ion to hydroxyl ion ratios for pastes containing CaC1 was higher than the pastes containing NaCl. Other investigators have postulated that the chloride to hydroxyl ionic ratio 18 important in the corrosion steel in chloride contaminated concrete. The results of this combined electrochemical and pare solution work agrees with the result s suggested by these earlier investigators, that increasing Cl-to Oh ratios results in increased corrosivity. Thus, the pare solution analisys gives Insight to the different corrosion behavior found with NaCl2 and CaC12 containing concretes.